Computer Modeling Of Electromechanical Systems - Sagatov Miraziz Vorisovich (International Journal of Advanced Science and Technology, 2020)
Among modern technical means of industrial, energy and transport purposes, an important role is given to electromechanical objects. Thanks to the massive use of such objects in various fields of human activity, work has been intensively carried out to improve them over the years. Existing common software for computer modeling are characterized by certain opportunities for implementing a structure-oriented approach. In particular, the representative of such tools is the MatLab / Simulink package. However, its application requires significant preliminary preparation of the simulation problem, which consists in creating the appropriate algorithms to supplement the set of functional blocks with new ones, including alternative ones, which make it possible to efficiently solve the problems posed. A method of structuralalgorithmic modeling of electromechanical systems is proposed, which is an application of a set of models implemented in the form of a library of basic algorithms obtained on the basis of a detailed mathematical description of the processes occurring in the links of electromechanical systems. The main advantages of this modeling method are that, firstly, it gives a visual representation of an arbitrarily complex simulated system; secondly, it allows to describe objects in the same way using models of any kind, including pulse transition or transfer functions, and the rules for connecting individual blocks; thirdly, it makes it possible to determine the characteristics of the entire system as a whole and its individual parts, to analyze and synthesize complex objects containing links with both concentrated and distributed parameters.